Validation of the Spanish Childhood Trauma Questionnaire-Short Form in adolescents with suicide attempts - García-Fernández, Ainoa; Martínez-Cao, Clara; Sánchez-Fernández-Quejo, Alberto; Bobes-Bascarán, Teresa; Andreo-Jover, Jorge; Ayad-Ahmed, Wala; Cebriá, Ana Isabel; Díaz-Marsá, Marina; Garrido-Torres, Nathalia; Gómez, Sandra; González-Pinto, Ana; Grande, Iria; et al. (Frontiers in Psychology, 2024)
Background Child maltreatment is associated with a higher probability of mental disorders and suicidal behavior in adolescence. Therefore, accurate psychometric instruments are essential to assess this. Objective To validate the Spanish version of the Childhood Trauma Questionnaire-Short Form (CTQ-SF) in adolescents with suicide attempts. Methods Multisite cohort study of 208 adolescents with suicide attempts using data from the following scales: Mini International Neuropsychiatric Interview (MINI), Columbia Suicide Severity Rating Scale (C-SSRS), Patient Health Questionnaire (PHQ-9), and CTQ-SF. Statistical analysis: CTQ-SF scores analyzed by descriptive statistics. Internal consistency: McDonald’s omega and Cronbach’s alpha. Concurrent validity with PHQ-9 and C-SSRS scores: Spearman correlation coefficient. Structural validity: Confirmatory factor analysis. Results Floor and ceiling effects: Physical abuse and neglect as well as sexual abuse demonstrated high floor effects (50.0, 35.1, and 61.1% of adolescents, respectively). No ceiling effects were found. The CTQ-SF had excellent internal consistency (McDonald’s omega = 0.94), as did the majority of its subscales (Cronbach’s alpha 0.925–0.831) except for physical neglect (0.624). Its concurrent validity was modest, and the emotional neglect subscale had the lowest Spearman correlation coefficients (0.067–0.244). Confirmatory factor analysis: Compared with alternative factor structures, the original CTQ-SF model (correlated 5-factor) exhibited a better fit [S-B χ2 = 676.653, p < 0; RMSEA (90% CI = 0.076–0.097) = 0.087; SRMR = 0.078; CFI = 0.980; TLI = 0.978]. Conclusion The Spanish CTQ-SF is a reliable, valid instrument for assessing traumatic experiences in adolescents at high risk of suicide. It appears appropriate for use in routine clinical practice to monitor maltreatment in this group.